Review of the central African leaf chafer genus Entypophana Moser, 1913 (Coleoptera: Scarabaeidae: Melolonthinae: Schizonychini) - Sehnal, Richard (Zootaxa, 2017)
The genus Entypophana Moser, 1913 is revised. Entypophana njiapanda new species from Tanzania is described, E. apicata Moser, 1913 (type species, by present designation), E. biapicata Moser, 1913, E. hulstaerti Burgeon, 1946, E. lujai Moser, 1917 and E. maynei Burgeon, 1946, are redescribed and lectotypes for E. biapicata, E. hulstaerti, E. lujai and E. maynei are designated. An identification key is provided and photographs illustrate external morphology and male genitalia. A distribution map of the currently known species of Entypophana is provided.